2021
DOI: 10.1097/inf.0000000000003015
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Clinical Profile of Sapovirus-associated Acute Gastroenteritis in Early Childhood

Abstract: Background: Sapovirus is increasingly recognized as an important cause of acute gastroenteritis (AGE) in children. We identified risk factors and characterized the clinical profile of sapovirus AGE in a birth cohort in León, Nicaragua. Methods: We conducted a case-control study nested within a birth cohort (n = 444). Fieldworkers conducted weekly household AGE surveillance. AGE stools were tested for sapovirus by reverse transcriptase quantitative polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 32 publications
2
15
2
Order By: Relevance
“…The Sapovirus-Associated Gastro-Enteritis (SAGE) study is a population-based birth cohort study in León, Nicaragua, described previously. 4 This cohort provided a platform to access a sample of all ages to understand the seroprevalence of SARS-CoV-2 in a Latin American context, and to examine differences in participant characteristics by evidence of prior infection. The study population included high-income families in the city center and low-income families in peri-urban neighborhoods, creating a scientifically-informative gradient to evaluate socioeconomic and environmental risk factors for SARS-CoV-2 infection.…”
Section: Methodsmentioning
confidence: 99%
“…The Sapovirus-Associated Gastro-Enteritis (SAGE) study is a population-based birth cohort study in León, Nicaragua, described previously. 4 This cohort provided a platform to access a sample of all ages to understand the seroprevalence of SARS-CoV-2 in a Latin American context, and to examine differences in participant characteristics by evidence of prior infection. The study population included high-income families in the city center and low-income families in peri-urban neighborhoods, creating a scientifically-informative gradient to evaluate socioeconomic and environmental risk factors for SARS-CoV-2 infection.…”
Section: Methodsmentioning
confidence: 99%
“…These data suggest that first sapovirus infections provide immunity against homologous infections, but little protection against infections of different genogroups, and possibly different genotypes. Further, the low incidence of symptomatic sapovirus episodes in the first months of life in epidemiological studies supports early protection from maternal immunity [210,239].…”
Section: Immune Protection Against Sapovirusmentioning
confidence: 79%
“…Sharing clinical characteristics with closely-related noroviruses, common symptoms of sapovirus gastroenteritis include vomiting and diarrhea [210]. Farkas, et al reported the seroprevalence of sapovirus (Mex340 strain) in children between 20 and 24 months of age involved in a birth cohort was greater than 90%, showing the high incidence of infections in early childhood [211].…”
Section: Burden Of Disease Across the Ages And State Of Vaccine Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sapovirus-Associated Gastro-Enteritis (SAGE) study is a population-based birth cohort study in León, Nicaragua, described previously. 11 This cohort provided a platform to access a sample of all ages from public health facility records, capturing a large and representative sample of this large urban area to understand the seroprevalence of SARS-CoV-2 in a Nicaraguan context, and to examine differences in participant characteristics by evidence of prior infection. The study population included high-income families in the city center and low-income families in peri-urban neighborhoods, creating a scientificallyinformative gradient to evaluate socioeconomic and environmental risk factors for SARS-CoV-2 infection.…”
Section: Study Design and Populationmentioning
confidence: 99%